Pushing the Limits of Nucleic Acid Function - Curtis, Edward A (Chemistry (Weinheim an der Bergstrasse, Germany), 2022)
For many decades it was thought that information storage and information transfer were the main functions of nucleic acids. However, artificial evolution experiments have shown that the functional potential of DNA and RNA is much greater. Here I provide an overview of this technique and highlight recent advances which have increased its potency. I also describe how artificial evolution has been used to identify nucleic acids with extreme functions. These include deoxyribozymes that generate unusual products such as light, tiny motifs made up of fewer than ten nucleotides, ribozymes that catalyze complex reactions such as RNA polymerization, information-rich sequences that encode overlapping ribozymes, motifs that catalyze reactions at rates too fast to be followed by manual pipetting, and functional nucleic acids which are active in extreme conditions. Such motifs highlight the limits of our knowledge and provide clues about as of yet undiscovered functions of DNA and RNA.
Keywords: nukleové kyseliny; nukleotidy; RNA, Catalytic; supernova deoxyribozyme; DNA; Nucleic Acids; DNA, Catalytic; konformace nukleové kyseliny; DNA katalytická; Nucleic Acid Conformation; Nucleotides; deoxyribozyme; RNA; ribozyme; aptamer; in vitro selection; RNA katalytická